SPECIFIC SOCIAL AND PSYCHOLOGICAL CHARACTERISTICS OF PSYCHOLOGICAL SERVICE (Archive of Conferences, 2021)
The scientific article provides a theoretical approach to the organization of psychological services for adolescents. Psychological services for adolescents are based on the need for diagnostics and psychological prevention of various mental and emotional problems that arise in the performance of their duties, as well as the need for psychological correction.